Effect of Project-Based Teaching Strategies on Cognitive and Social Skills Development of Primary School Pupils in Ogun East Senatorial District - Ogunyemi, F. Taiwo; Oladele, Michael T.; Gbadegesin, Motunrayo. A; Zakariyyah, Fatimah; Sokoya, Taiwo Omobolanle (Kashere Journal of Education, 2025)
The study investigated the effect of the project-based teaching strategy on the cognitive and social skills development of primary school pupils in the Ogun East Senatorial District of Ogun State. The main objective of this study was to investigate the main effect of project-based teaching strategies, attitude, and gender on cognitive and social skill development of primary school pupils. Quasi-experimental research design was adopted for the study. The population was primarily six (6) pupils. A sample size of 154 pupils selected from four (4) public primary schools participated in the study. Enumeration method was used to select the Ogun State senatorial district. In order to choose a local government area, purposeful sampling was employed. Two schools were assigned to an experimental group and one to a control group using convenience sampling. Crombach Alpha was used to validate the instrument on cognitive and social skills development at an index of 0.821. The moderating variables of gender and learners’ attitudes were examined in relation to the outcome variable. The data were analysed using a method called Analysis of Covariance (ANCOVA) to address the research questions and test the hypotheses, with a significance level set at 0.05 The results of the study indicate that the Experimental Group (project-based teaching strategies) performed better (mean score = 99.72) than the Control group (conventional strategy) (with a mean score of 92.9), confirming that treatment had differential effects on Cognitive Skills development among primary school pupils. Similarly, there is a significant main effect of treatment (project-based strategy) on Social Skills Development among Primary School pupils (F (2, 141) = 6.090, P < .05 = 0.003). It was concluded based on the findings of the study that the project-based teaching strategy had a significant effect on the cognitive and social skills development of primary school pupils. Based on the findings of the study, step-by-step, user-friendly teaching guides on project-based strategies should be designed by teachers to enhance the readiness and interest of primary school pupils in learning.